Afro-Latin American Pharmacogenetics of CYP2D6, CYP2C9, and CYP2C19 in Dominicans: A Study from the RIBEF-CEIBA Consortium - Mariela Guevara; Fernanda Rodrigues-Soares; Carla González de la Cruz; Fernando de Andrés; Ernesto Rodríguez; Eva Peñas-Lledó; Adrián LLerena; CEIBA Consortium of the Ibero-American Network of Pharmacogenetics and Pharmacogenomics RIBEF (MDPI AG, 2024)
Background/Objectives: Research on pharmacogenetic variability in response to prescribed drugs and across ethnic groups is essential for personalized medicine, particularly in admixed and unstudied populations. For the first time, this study examines CYP2D6, CYP2C9, and CYP2C19 alleles and genotypes in 197 healthy volunteers from the Dominican Republic, as part of the RIBEF-CEIBA collaborative network. Methods: The analysis focuses on the participants' tri-hybrid genomic ancestry, with CYP alleles determined by real-time PCR and molecular ancestry inferred using 90 AIMs. Linear regression was used to associate ancestry components with CYP frequencies. Results: The average ancestry was 23.8% European, 42.6% Native American, and 33.6% African, the latter being higher than in most Latin American populations. Native American ancestry was also higher than expected. Predicted phenotype frequencies based on genotypes were 4.2% poor metabolizers (gPMs) and 3.6% ultrarapid metabolizers (gUMs) for CYP2D6, as well as 3% gPMs, 22.8% rapid metabolizers (gRMs), and 1.5% gUMs for CYP2C19. No gPM individuals were observed for CYP2C9. Certain alleles associated with decreased CYP2D6 activity (*17 and *29) and increased CYP2C19 activity (*17 and gUMs) were positively linked with African ancestry and negatively with Native American ancestry. Rare CYP2C9 alleles (*5 and *6) with clinical relevance were additionally found. Conclusions: These findings build on previous results from the RIBEF-CEIBA collaborative network, demonstrating differences in allele frequencies of CYP2D6, CYP2C9, and CYP2C19 in relation to genomic ancestry. In summary, ethnicity must be considered in the development of pharmacogenetic guidelines for clinical application, research, and regulation to avoid widening the biotechnology gap and to allow Personalized Medicine to reach the entire world population.